Canine prostatic cancer cell line (LuMa) with osteoblastic bone metastasis. Issue 9 (29th April 2020) - Elshafae, Said M.; Dirksen, Wessel P.; Alasonyalilar‐Demirer, Aylin; Breitbach, Justin; Yuan, Shiyu; Kantake, Noriko; Supsavhad, Wachiraphan; Hassan, Bardes B.; Attia, Zayed; Alstadt, Lucas B.; Rosol, Thomas J.
Abstract: Background: Osteoblastic bone metastasis represents the most common complication in men with prostate cancer (PCa). During progression and bone metastasis, PCa cells acquire properties similar to bone cells in a phenomenon called osteomimicry, which promotes their ability to metastasize, proliferate, and survive in the bone microenvironment. The mechanism of osteomimicry resulting in osteoblastic bone metastasis is unclear. Methods: We developed and characterized a novel canine prostatic cancer cell line (LuMa) that will be useful to investigate the relationship between osteoblastic bone metastasis and osteomimicry in PCa. The LuMa cell line was established from a primary prostate carcinoma of a 13‐year old mixed breed castrated male dog. Cell proliferation and gene expression of LuMa were measured and compared to three other canine prostatic cancer cell lines (Probasco, Ace‐1, and Leo) in vitro. The effect of LuMa cells on calvaria and murine preosteoblastic (MC3T3‐E1) cells was measured by quantitative reverse‐transcription polymerase chain reaction and alkaline phosphatase assay. LuMa cells were transduced with luciferase for monitoring in vivo tumor growth and metastasis using different inoculation routes (subcutaneous, intratibial [IT], and intracardiac [IC]). Xenograft tumors and metastases were evaluated using radiography and histopathology. Results: After left ventricular injection, LuMa cells metastasized to bone, brain, and adrenal glands. IT injections induced tumors with intramedullary new bone formation. LuMa cells had the highest messenger RNA levels of osteomimicry genes ( RUNX2, RANKL, and Osteopontin [OPN]), CD44, E‐cadherin, and MYOF compared to Ace‐1, Probasco, and Leo cells. LuMa cells induced growth in calvaria defects and modulated gene expression in MC3T3‐E1 cells. Conclusions: LuMa is a novel canine PCa cell line with osteomimicry and stemness properties. LuMa cells induced osteoblastic bone formation in vitro and in vivo. LuMa PCa cells will serve as an excellent model for studying the mechanisms of osteomimicry and osteoblastic bone and brain metastasis in prostate cancer.